Some new formulas on the K-Fibonacci numbers - Falcon, Sergio (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this paper, we find some formulas for finding some special sums of the k-Fibonacci or the k-Lucas numbers. We find also some formulas that relate the k-Fibonacci or the k–Lucas numbers to some sums of these numbers..